Method for the design of variable fractional delay filters with coefficient-dependence relation - ZHUANG Ling; LIU Ying; SONG Shiwei (Tongxin xuebao)
Aiming at the complexity problem in the design of variable fractional delay filters, a design method was considered. Time-domain interpolation and Taylor series expansion were integrated to configure the coefficient of Farrow structure, and the corresponding filter related formula was derived. The designed filter had coefficient-dependence relation, nearly half of the filter coefficients were independent, and an implemented structure of low-complexity filter was obtained. Theoretical derivation and simulation verification were conducted from the aspects of complexity, magnitude response, group delay, and error. The analysis shows that the proposed method can effectively reduce the complexity and computational cost of variable fractional delay filters.